Analisis Manfaat Ekonomi Taman Hutan Raya Sultan Syarif Hasyim Pekanbaru - Muhibbin Annas; Suardi Tarumun; Tengku Nurhidayah (Dinamika Lingkungan Indonesia, 2016)
The aims of these research are ; 1) to analyze the economic value of Taman Hutan Raya Sultan Syarif Hasyim, consist of : log value, carbon value and reducing soil erosion value. 2) to analyze some alternatives policies to meet the sustainable management of Tahura Sultan Syarif Hasyim, Pekanbaru. The research was held on Taman Hutan Raya Sultan Syarif Hasyim, Pekanbaru from August to November 2014. The methode of research is survey and the analysist methode is descriptive kuantitative analysist. The primary data are collected with line plot sampling and soil sampling. The results show that the economic value of 2,412 ha (the remaining Tahura area covered by forest) are: log value IDR 2,434,799,820.00 year-1, carbon value IDR 18,718,898,525.19 year-1 consist: carbon sink value IDR 5,919,446,552.45 year-1 and carbon saturation value IDR 12,799,451,972.74 year-1. The reducing erosion value IDR 83,349,849,057.00 year-1. To optimalize the economic value, the policies are: 1) To restore the Tahura area directly into conservation forest with forest cover. 2) To restore the Tahura area gradually into conservation forest with forest cover and 3) To restore Tahura by collaborating management.